Quantitative Characterization for Pore Connectivity, Pore Wettability, and Shale Oil Mobility of Terrestrial Shale With Different Lithofacies—A Case Study of the Jurassic Lianggaoshan Formation in the Southeast Sichuan Basin of the Upper Yangtze Region in Southern China - Zhang, Kun; Jiang, Zhenxue; Song, Yan; Jia, Chengzao; Yuan, Xuejiao; Wang, Xueying; Zhang, Liwen; Han, Fengli; Yang, Yiming; Zeng, Yao; Liu, Pei; Tang, Liangyi; et al. (Frontiers in Earth Science, 2022)
Some major hydrocarbon-bearing basins are rich in shale with terrestrial facies in China, which may provide abundant terrestrial shale oil and gas resources. This work studied the Jurassic Lianggaoshan Formation in the Southeast Sichuan Basin of the upper Yangtze Region. Core samples were chosen for the total organic carbon content and mineral composition analyses to classify shale lithofacies. Afterward, pore connectivity, pore wettability, and shale oil mobility with different lithofacies were characterized by spontaneous imbibition, nuclear resonance, and centrifugation. Conclusions are as follows: the pore connectivity of organic-rich clay shale was mostly between moderate to good with oil-prone wettability and high mobile oil saturation. The organic-rich mixed shale has moderate to good pore connectivity, water-prone wettability, and the highest mobile oil saturation. Organic matter–bearing clay shale has bad to moderate pore connectivity. Meanwhile, its pore wettability covers oil wetting, mixed wetting, oil-prone wetting, and water-prone wetting. Its mobile oil saturation was moderate. Regarding organic matter–bearing mixed shale, the pore connectivity was bad to moderate with mixed-wetting pore wettability and moderate mobile oil saturation.